Assessment of menopausal symptoms using modified menopause rating scale (MRS) in women of Northern India - Khatoon, Fareha; Sinha, Parul; Shahid, Sana; Gupta, Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Menopause is defined as complete cessation of menses for twelve months or more. It is a normal physiological change experienced by middle aged women and some of the menopausal symptoms experienced by these women can be severe enough to affect their normal daily activities. Methods: An observational cross sectional study was carried out in the Department of Obstetrics and Gynecology, Era’s Lucknow Medical College and hospital, Lucknow for a period of one year.300 patients who had attained menopause were analyzed. Menopausal symptoms were assessed using Modified Menopause Rating Scale (MRS). Results: Majority of patients attained menopause at the age of 50-54 years and the calculated mean age came to be 50.33±5.26. The most common symptom reported was joint and muscular discomfort (87%), depressive mood (70%), heart discomfort (60.3%), physical and mental exhaustion (60%), sleep problems (56%). The most classical symptom of menopause i. e. hot flushes was reported in 53.3%. Prevalence of other symptoms in decreasing order were irritability (46.6%), anxiety (40.3%), bladder problem (26%), dryness of vagina (23%), sexual problems (20%). The menopausal symptoms were found to be more prevalent in women of lower socio economic strata and those who had no formal education and this difference was found to be statistically significant. Conclusions: There is a high burden of postmenopausal symptoms which have shown an increasing trend with advancement of age. This calls for establishment of specific health intervention for postmenopausal women through the existing health centres by having geriatric clinics.